(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The design and analysis of a quadcopter drone frame using finite element analysis (FEA) methods are presented in this work. The goal is to save weight and material consumption while optimising the frame’s performance attributes and structural integrity. The finite element approach offers a reliable foundation for modelling the behaviour of structures under different loading scenarios, enabling effective design iterations and enhancements. Through the use of FEA, this study seeks to improve the stability, durability, and aerodynamic efficiency of the frame, which will eventually aid in the creation of more dependable and effective quadcopter drones.